Design and Implementation of a Distributed Virtual Environment Development Platform - Yongjun, Wang; Yijie, Wang; Long, Zhao; Sikun, Li (International Journal of Virtual Reality, 2000)
A novel design method of the distributed virtual environment development platform is studied in this paper. First, a language model based on complex behaviors for virtual environment is proposed to improve the ability of behavior modeling. Then a computing model of virtual environment based on the complex behavior is proposed to formalize the simulation computing unit of virtual environment extended to build up an distributed architecture of virtual environment application. The performance requirements of virtual environment are analyzed, and the concept of scalability is redefined. Some strategies of dynamic load distribution are discussed to maintain the performance of distributed virtual environment. Finally, YHVRP, a prototype system of distributed virtual environment development system, is introduced.